The Individual Work Performance Questionnaire: Psychometric Properties of the Italian Version - Silvia Platania; Martina Morando; Stefania Valeria Gruttadauria; Linda Koopmans (MDPI AG, 2023)
Individual work performance can be defined as individual behaviour capable of generating value and a competitive advantage for the organization. Furthermore, this construct is linked to other fundamental variables that constitute worker well-being, such as job satisfaction and engagement. Although important, a complete measure of individual work performance is still lacking in the Italian context. The objective of this work is to validate the Individual Work Performance Questionnaire (IWPQ) within the Italian organisational context. The IWPQ is a multi-dimensional construct consisting of task performance, contextual performance, and counterproductive work behavior. To investigate the psychometric properties of the Italian IWPQ, 1053 participants were enrolled, whose ages ranged between 19 and 69 years. EFA, CFA, and MCFA analyses were performed to test the structural factors of the IWPQ. The results supported the validity of the IWPQ in the Italian context; the final structure consisted of 17 items. Multigroup confirmatory factor analysis showed that the factor solution was invariant across both gender and occupational categories and found evidence of metric, uniqueness, scalar, and structural invariance. Convergent validity was also tested and demonstrated. Adequate studies on the importance of individual performance can be used to better understand and distinguish the different components affecting performance.